Spawning potential ratio of comercially important spiny lobster in Donggala Waters Central Sulawesi - Muh Saleh Nurdin; Salim Salim; Nur Hasanah; Aswad Eka Putra; Teuku Fadlon Haser; Akbar Marzuki Tahya; Novalina Serdiati; Kasim Mansyur; Madinawati Madinawati (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
Currently, spiny lobster fishery in Indonesia ranks third as an export commodity from the crustacean subphylum after shrimp and blue swimming crab – mud crab. Most of the spiny lobster export needs still rely on wild population resulting in fishing pressure. To ensure the sustainability of spiny lobster stocks, information of the Spawning Potential Ratio (SPR) is needed. This study aims to analyze SPR of spiny lobsters of Panulirus femoristriga and P. versicolor species. The research was conducted in May − November 2022 in Donggala Regency waters. SPR analysis uses the Length-Based SPR method. The results showed that the stock status of P. femoristriga and P. versicolor had experienced growth overfishing and recruitment overfishing with estimated SPRs of 17 and 11%, respectively. Fishing regulations are needed to maintain a sustainable spiny lobster fishery through increased participation of stakeholders in the implementation, monitoring and evaluation of the regulations set by the government. In addition, it is necessary to reduce of efforts 27 − 33% from the current exploitation rate to E50 0.28.